Narcissism in William Shakespeare’s Drama Coriolanus - Dinda Rahmadani; Meisya Audreyanna Azzahra; Yosi Evelyn Tondang; Naya Islah Nabilah; Syamsul Bahri (STIKes Ibnu Sina Ajibarang, 2025)
Human behavior and psychological conflict often become central elements in literary works, especially in drama, where characters are shaped through tension, pride, emotion, and social expectation. Shakespeare’s Coriolanus presents a character whose sense of pride, identity, and honor creates ongoing conflict with the society around him. This study aims to analyze the forms of narcissism expressed by Coriolanus using Otto Kernberg’s fourfold theory: healthy, grandiose, vulnerable, and malignant. A qualitative descriptive method was applied through textual analysis and library research, focusing on key scenes that reveal his psychological development. The results show that grandiose narcissism is the most dominant type (36%), as seen in scenes where Coriolanus belittles the plebeians and rejects their approval, reflecting his rigid superiority as a Roman patrician. Healthy narcissism appears least (10%), found only in early moments such as his genuine pride after the battle at Corioles before political pressure intensifies his arrogance. Meanwhile, vulnerable and malignant narcissism each appear at 27%, shown when he collapses into shame after public rejection and later seeks revenge by joining Aufidius. These findings illustrate that Coriolanus’s downfall is shaped by the progression of his narcissism from pride to contempt, fragility, and destruction.